Indonesian Muslims and Arabic Language: Leaves and Light in the Realm of Religi-Linguistics - Widiya Yul; Riko Andrian (ALSINATUNA, 2024)
Low achievement in Arabic language learning among students remains a critical issue in Indonesia. This study seeks to refine the paradigm of Arabic language education by aligning it with the learning objectives and socio-cultural tendencies of society and students. Despite various innovations in curriculum and pedagogy, outcomes remain suboptimal. This research proposes a new paradigm that integrates Arabic language education with the cultivation of Islamic religious character (religi-linguistic), positioning Islamic values as central while using Arabic as a strategic tool to achieve these objectives. Employing a qualitative approach grounded in grounded theory, the study develops this paradigm within Ma’had Al-Jāmi’ah (Islamic boarding schools) at State Islamic Higher Education Institutions (PTKIN) in Indonesia. The findings highlight the interdisciplinary framework of religi-linguistics, which includes: (1) Islam as the foundational discipline and goal; (2) religious character as the primary indicator; (3) Arabic as the medium; (4) structured interdisciplinary steps in Arabic language learning; and (5) modeling and environmental design as essential strategies.This study urges scholars and policymakers to reevaluate traditional paradigms and adopt this integrated approach, offering a more cohesive and purpose-driven model for Arabic education that addresses both linguistic proficiency and religious character development.